Identification of BAP1 mutation as a common mutation correlated with tumor mutation burden and immune infiltration in kidney renal clear cell carcinoma. Issue 1 (31st December 2022) - Xu, Jin-Zhou; Xia, Qi-Dong; Lu, Jun-Lin; Xun, Yang; Liu, Chen-Qian; Sun, Jian-Xuan; Li, Cong; Hu, Jia; Wang, Shao-Gang
Abstract : Kidney renal clear cell carcinoma (KIRC) is the predominant pathological subtype of kidney cancer and is categorized as immunotherapy responsive. Hence, immunotherapy has become a worthwhile therapy for KIRC. Furthermore, tumor mutation burden (TMB) has been regarded as the most prevalent biomarker to predict immunotherapy response. Accordingly, we spent the effort to characterize the status and the predictive potential for immunotherapy response of gene mutations in KIRC. In this study, we identified common somatic mutations in KIRC patients from The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), and UTokyo cohorts in cBioportal database. BRCA1-related protein 1 (BAP1) was identified as the only common gene mutation related to TMB and overall survival. We finally explored whether mutation of BAP1 was related to immune response and immune infiltration. In brief, we identified and demonstrated that BAP1 mutations commonly occurred in KIRC patients, associated with lower TMB, and indicating a poorer prognosis. Furthermore, BAP1 mutation reversed its function as a tumor suppressor via influencing Mast cells' quantity. These findings cast light on the predictive value of BAP1 to evaluate immunotherapeutic sensitivity and presented a potential target for KIRC treatment.